Community forests as beacons of conservation: Enabling local populations monitor their biodiversity - Fa, J.E.; Luiselli, L. (Wiley, 2024)
Habitat fragmentation is one of the main threats to biodiversity in Africa. In this article, we highlight the importance of conserving the Guinean forests of West Africa, which are rich in biodiversity and endemism but threatened by habitat loss, degradation and fragmentation. The size of forest patches is critical, with larger fragments containing more species than smaller ones. The protection of intact, dense forest patches is vital for any conservation strategy in West Africa, but improving the management of forests that are already used for logging and hunting is also essential. Community forests (CFs) can play a crucial role in conservation, especially if there is a substantial network that can promote ecological connectivity. However, biomonitoring in CFs remains a challenge due to inadequate resources. By developing standardised, easy-to-apply and inexpensive methods for biomonitoring, communities can be involved in biomonitoring instead of relying solely on scientists and expensive equipment. We present a monitoring framework here where we suggest local communities should become the main agents for biomonitoring in their own forests; we highlight a five-step scheme. The importance of the various CFs in terms of conservation should be made through a combination of accurate, standardised face-to-face interviews with selected persons in the target communities and biomonitoring be based on the RAPELD scheme. The latter will be implemented after specifically training local ‘wise’ persons. We are proposing a kind of ‘citizen science’ scheme, applied to enhance the ability of local communities to monitor their own biodiversity.